Jupiter’s Metastable Companions - Sarah Greenstreet; Brett Gladman; Mario Jurić (The Astrophysical Journal Letters, 2024)
Jovian co-orbitals share Jupiter’s orbit and exhibit 1:1 mean-motion resonance with the planet. This includes >10,000 so-called Trojan asteroids surrounding the leading (L4) and trailing (L5) Lagrange points, viewed as stable groups dating back to planet formation. A small number of extremely transient horseshoe and quasi-satellite co-orbitals have been identified, which only briefly (<1,000 yr) exhibit co-orbital motions. Via an extensive numerical study, we identify for the first time some Trojans that are certainly only “metastable”; instead of being primordial, they are recent captures from heliocentric orbits into moderately long-lived (10 kyr–100 Myr) metastable states that will escape back to the scattering regime. We have also identified (1) the first two Jovian horseshoe co-orbitals that exist for many resonant libration periods and (2) eight Jovian quasi-satellites with metastable lifetimes of 4–130 kyr. Our perspective on the Trojan population is thus now more complex as Jupiter joins the other giant planets in having known metastable co-orbitals that are in steady-state equilibrium with the planet-crossing Centaur and asteroid populations; the 27 identified here are in agreement with theoretical estimates.